EBV stimulates TLR‐ and autophagy‐dependent pathways and impairs maturation in plasmacytoid dendritic cells: Implications for viral immune escape. Issue 1 (30th October 2012) - Severa, Martina; Giacomini, Elena; Gafa, Valerie; Anastasiadou, Eleni; Rizzo, Fabiana; Corazzari, Marco; Romagnoli, Alessandra; Trivedi, Pankaj; Fimia, Gian Maria; Coccia, Eliana Marina
<x xml:space="preserve">Abstract</x> Plasmacytoid DCs (pDCs) are crucial mediators in the establishment of immunity against most viruses, given their extraordinary capacity to produce a massive quantity of type I IFN. In this study we investigate the response of pDCs to infection with EBV, a γ‐herpes virus that persists with an asymptomatic infection in immunocompetent hosts, although in certain conditions it can promote development of cancers or autoimmune diseases. We show that high amounts of type I IFNs were released from isolated pDCs after exposure to EBV by a mechanism requiring TLRs and a functional autophagic machinery. We next demonstrate that EBV can infect pDCs via viral binding to MHC class II molecule HLA‐DR and that pDCs express EBV‐induced latency genes. Furthermore, we observe that EBV is able to induce activation but not maturation of pDCs, which correlates with an impaired TNF‐α release. Accordingly, EBV‐infected pDCs are unable to mount a full T‐cell response, suggesting that impaired pDC maturation, combined with a concomitant EBV‐mediated upregulation of the T‐cell inhibitory molecules B7‐H1 and ICOS‐L, could represent an immune‐evasion strategy promoted by the virus. These mechanisms might lead to persistence in immunocompetent hosts or to dysregulated immune responses linked to EBV‐associated diseases.